2017
DOI: 10.11604/pamj.2017.28.230.13836
|View full text |Cite
|
Sign up to set email alerts
|

Rural-urban disparity in lung function parameters of Nigerian children: effects of socio-economic, nutritional and housing factors

Abstract: IntroductionThe effect of socio-demographic and nutritional factors on lung functions of African children is poorly studied. This study set out to determine the effects of these factors on lung functions of Nigerian school children.MethodsRural and urban secondary schools students in Ilesa, Nigeria were selected by multistage sampling. The socio-demographic, nutritional status as well as lung function parameters measured using incentive Spirometry (MIR Spirolab III srl, Italy) of the children were obtained and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 23 publications
(51 reference statements)
2
21
0
Order By: Relevance
“…The pathophysiology of biomass smoke airway damage is not yet fully understood but a recent study in China suggests that biomass smoke probably causes disease through damage to the small airways which is consistent with the association with FEF 25–75 % observed in this study [39]. Nutritional status has been previously found to affect lung function [38,40,41,42]. In Nigeria, Kuti et al assessed the effect of nutritional status in 250 children and found that underweight children had significantly lower lung function than normal weight children [38].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The pathophysiology of biomass smoke airway damage is not yet fully understood but a recent study in China suggests that biomass smoke probably causes disease through damage to the small airways which is consistent with the association with FEF 25–75 % observed in this study [39]. Nutritional status has been previously found to affect lung function [38,40,41,42]. In Nigeria, Kuti et al assessed the effect of nutritional status in 250 children and found that underweight children had significantly lower lung function than normal weight children [38].…”
Section: Discussionsupporting
confidence: 85%
“…Children in urban sites, those with cough, exposure to biomass smoke and underweight had lower lung function. The association between lung function and, cough, urbanization, underweight and biomass smoke exposure has been previously reported [15,36,37,38]. In the current study, the association between biomass smoke exposure and lung function was found only for FEF 25–75 %, a key marker of small airway dysfunction.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Many people in developing countries rely on biomass such as wood and dung as an energy source for cooking and also lighting. Exposure to smoke from the combustion of biomass can lead to respiratory diseases [71] and other symptoms including eye irritation [38]. Survey studies performed in Vietnam, Ethiopia, and Bangladesh report positive impacts from the installation of biogas digesters in smallholder farms and households [36,38,51].…”
Section: Social Aspectmentioning
confidence: 99%
“…Most reports have focused on comparisons of mean differences in spirometric indices based on demographics and health status. 14 , 15 Few have interpreted their findings using globally accepted reference standards like the Global Lung Initiative (GLI-2012). The GLI-2012 has been shown to be applicable in children and adults (3-95 years) from different countries as it eliminates age, gender, ethnic, and height bias in lung function interpretation.…”
Section: Introductionmentioning
confidence: 99%